β-Glucan as Trained Immunity-Based Adjuvants for Rabies Vaccines in Dogs - Paris, Simon; Chapat, Ludivine; Martin-Cagnon, Nathalie; Durand, Pierre-Yves; Piney, Lauriane; Cariou, Carine; Bergamo, Pierre; Bonnet, Jeanne-Marie; Poulet, Hervé; Freyburger, Ludovic; De Luca, Karelle (Frontiers in Immunology, 2020)
The mechanisms of trained immunity have been extensively described in vitro and the beneficial effects are starting to be deciphered in in vivo settings. Prototypical compounds inducing trained immunity, such as β-glucans, act through epigenetic reprogramming and metabolic changes of innate immune cells. The recent advances in this field have opened new areas for the development of Trained Immunity-based Adjuvants (TIbA). In this study, we assessed in dogs the potential immune training effects of β-glucans as well as their capacity to enhance the adaptive immune response of an inactivated rabies vaccine (Rabisin®). Injection of β-glucan from Euglena gracilis was performed one month before vaccination with Rabisin® supplemented or not with the same β-glucan used as adjuvant. Trained innate immunity parameters were assessed during the first month of the trial. The second phase of the study was focused on the ability of β-glucan to enhance adaptive immune responses measured by multiple immunological parameters. B and T-cell specific responses were monitored to evaluate the immunogenicity of the rabies vaccine adjuvanted with β-glucan or not. Our preliminary results support that adjuvantation of Rabisin® vaccine with β-glucan elicit a higher B-lymphocyte immune response, the prevailing factor of protection against rabies. β-glucan also tend to stimulate the T cell response as shown by the cytokine secretion profile of PBMCs re-stimulated ex vivo. The potential of TIbA to provide increased immunogenicity of specific vaccines while conferring broad non-specific responses is only starting to be investigated. Our data are providing new insights on the impact of trained immunity on the adaptive immune response to vaccines in dogs. The administration of β-glucan, one month before or simultaneously to Rabisin® vaccination give promising results for the generation of new TIbA candidates. In the context of finding new approaches to vaccine design, trained immunity-based adjuvants could trigger a broad innate response to unrelated or bystander pathogens and a specific response to vaccines.